2021
DOI: 10.33365/ji-mr.v2i1.1061
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Penggunaan Aplikasi Youtube Dan Facebook Terhadap Hasil Belajar Matematika

Abstract: The purpose of this study was to determine the effect of using YouTube and Facebook applications on mathematics learning outcomes. This research uses quantitative research. The subjects of this study were students of prospective Mathematics Teachers at the Indonesian Technocrat University and UIN Raden Intan Lampung batch 2018 with 20 respondents. This research was conducted in 5 stages namely; 1) Distributing questionnaires in the form of Google Forms, 2) Assessing the results of prospective Mathematics Teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…The literature review data in this research was identified from Google Scholar. The stages of this research study are: 1) defining the topic or problem to be reviewed, 2) identifying relevant reference materials through Google Scholar, 3) selecting the results obtained from Google Scholar according to the specified criteria, 4) compiling a synthesis matrix of the results obtained, and 5) concluding the review results (Parinata & Puspaningtyas, 2022). The Systematic Literature Review (SLR) research stages are presented in Figure 1 as follows.…”
Section: Methodsmentioning
confidence: 99%
“…The literature review data in this research was identified from Google Scholar. The stages of this research study are: 1) defining the topic or problem to be reviewed, 2) identifying relevant reference materials through Google Scholar, 3) selecting the results obtained from Google Scholar according to the specified criteria, 4) compiling a synthesis matrix of the results obtained, and 5) concluding the review results (Parinata & Puspaningtyas, 2022). The Systematic Literature Review (SLR) research stages are presented in Figure 1 as follows.…”
Section: Methodsmentioning
confidence: 99%
“…After collecting the data, a descriptive analysis is conducted to present the current facts and provide a concise explanation. The research study follows several stages, including defining the topic, identifying relevant sources through Google Scholar, selecting results based on specific criteria, compiling a synthesis matrix of the results, and concluding the review findings (Parinata & Puspaningtyas, 2022). The process of Systematic Literature Review (SLR) is outlined in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Hasil belajar merupakan skill yang dimiliki siswa setelah mereka mendapatkan kemampuan belajarnya (Agus, 2021). Menurut Hordward Kingsley (Parinata, 2021) hasil belajar terbagi menjadi 3 macam, yakni;…”
Section: Pendahuluanunclassified